The Perception Towards Accounting Practices of Murabahah Among Accounting Students in Malaysia - Hassan, Nur Hidayah; Mohd Shariff, Ros Aniza; Ahmad, Hawa (2015)
The study focuses on Malaysia and the main aim is to investigate the perception of accounting students towards the existing accounting practices of Murabahah financing according to MFRS 118 and the guidelines of MASB TRi-4. The study utilizes inferential statistical analysis techniques, namely, the Mann-Whitney test and Kruskal-Wallis test, Pearson correlation analysis and Stepwise multiple regression analysis to assess the data. The results of the analysis indicated that there is a significant relationship between the respondents’ awareness of Murabahah financing and their education level as the higher the level education, the more the respondents are aware of Murabahah financing. The study found that there is a moderate acceptance of the existing accounting practices of Murabahah financing according to MFRS 118 and the guidelines of MASB TRi-4 among accounting students in Malaysia in terms of recognition, measurement and disclosure and presentation.While the study has some limitations, it is expected that it will give implications for Malaysian accounting standards setters in creating a framework for Murabahah financing in terms of the accounting treatments for recognition, measurement and disclosure and presentation. This study has the potential to make a contribution to the accounting education by the implementation of Islamic accounting practices in Malaysia, particularly with respect to identifying the impact of tertiary-level accounting courses and the perception of accounting students towards the existing accounting practices of Murabahah financing. Keywords: Murabahah, Islamic banking, Accounting Student, Accounting Education.